The idea of a university - Newman, John Henry, Saint, 1801-1890.; Turner, Frank M. (Frank Miller), 1944-2010. (New Haven : Yale University Press, 1996)
This edition of The idea of a University includes the full text of the original 1852 publication and four selections from the subsequently added "University Subjects" together with five essays by leading scholars that explore the background and the present-day relevance of Newman's themes
Introduction to interpretative essays : "Newman in his own day" / Martha McMackin Garland -- "Newman's university and ours" / Frank M. Turner -- "Theology and the university : Newman's idea and current realities" / George M. Marsden -- "The paradox of self in The idea of a university" / Sara Castro-Klarén -- "Newman and the idea of an electronic university" / George P. Landow.
Includes bibliographical references (pages 363-366).
Print version record.
English.
eBooks on EBSCOhost
Keywords: Newman, John Henry, -- Saint, -- 1801-1890.; Idea of a university (Newman, John Henry, Saint); Newman, John Henry -- 1801-1890; Newman, John Henry; Education, Higher -- Philosophy; Universities and colleges -- Philosophy; Universities and colleges; Universities; Enseignement supérieur -- Philosophie; Universités -- Philosophie; Universités.; universities (institutions); colleges (institutions); EDUCATION -- Higher; Universities and colleges; Education, Higher -- Philosophy; Universities and colleges -- Philosophy; Hochschule; Universiteiten; Doelstellingen